Analisis Sistem Kinerja Drainase Berbasis Sistem Informasi Geografis (SIG) di Lingkungan Universitas Lampung - Fikri, Aulia; Purwadi, Ofik Taupik; Perangin Angin, Geleng (Universitas Lampung, 2018)
Urban drainage systemare important. Drainage problems can cause puddle and flood. Therefore, it is needed an analysis and information about drainage system’s performance in Lampung University’s environment. The information of this data is in the form of digital based system that is Geographic Information System.Research is done at the environment of Lampung University, Bandar Lampung. The purpose of study is to know the drainage problem, drainage performance, handling concept, and database that is visualized based on GIS. So, it is expected to be useful and facilitate the policy holder and society to access the information.Based on research, formed a database GIS that is a result of spatial, hydrology, and hydraulics analysis is watersheds analysis, flood debt data, condition data, function, type, geometric and waterworks, puddle data and capacity of drainage. From those analysis obtained the drainage performance system that needed to have a physical and flow network connectivity repair. Also, the implementation of environmentally drainage concept with optimization the function of retention pond a way to manage water conservation is connected with drainage system. There are 4 pond and retention pond as handling plan. Keywords: Drainage, Watersheds Analysis, GIS, SIG, Geographics Information System.